1995
DOI: 10.1128/jb.177.6.1497-1504.1995
|View full text |Cite
|
Sign up to set email alerts
|

Gratuitous overexpression of genes in Escherichia coli leads to growth inhibition and ribosome destruction

Abstract: We attempted to test the idea that the relative abundance of each individual tRNA isoacceptor in Escherichia coli can be altered by varying its cognate codon concentration. In order to change the overall codon composition of the messenger pool, we have expressed in E. coli lacZ with the aid of T7 RNA polymerase and, separately, we have expressed a truncated tufB gene (designated ⌬tufB) with the aid of E. coli RNA polymerase so that their respective gene products individually accounted for 30% of the total bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
285
2
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(308 citation statements)
references
References 24 publications
20
285
2
1
Order By: Relevance
“…The mechanism of this effect is unclear. One possible explanation is that an unspecific`protein burden' causes starvation of the bacteria: it has been shown that overexpression of various proteins is accompanied by an uniform growth-rate inhibition (Dong et al, 1995). On the other hand, however, the growth inhibition appears to be stronger than expected (Kurland and Dong, 1996).…”
Section: Introductionmentioning
confidence: 82%
“…The mechanism of this effect is unclear. One possible explanation is that an unspecific`protein burden' causes starvation of the bacteria: it has been shown that overexpression of various proteins is accompanied by an uniform growth-rate inhibition (Dong et al, 1995). On the other hand, however, the growth inhibition appears to be stronger than expected (Kurland and Dong, 1996).…”
Section: Introductionmentioning
confidence: 82%
“…Thus, they hypothesized that as amino acid charging of tRNA becomes limiting, only the tRNAs that are robust to starvation can support high translation levels of heterologous protein expression. Therefore successful codon bias of a gene depends on maintaining high levels of charged tRNAs and minimizing levels of uncharged tRNAs which can inhibit translation (Bonomo & Gill 2005;Dong et al 1995;Harcum 2002;Welch, Govindarajan, et al 2009). …”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%
“…After the initial attempts to make vast quantities of the targeted protein have failed, the experimenters may, in desperation, study their cultures. They then find that the fully induced bacteria are behaving wierdly: they grow slowly (Springer et al, 1985;Franklyn and Schimmel, 1990;Menguito et al, 1993;Tubulekas and Hughes, 1993;Vind et al, 1993;Bowrin et al, 1994), they produce enhanced quantities of heat-shock proteins (Bahl et al, 1987;Parsell and Sauer, 1989;Vind et al, 1993;Dong et al, 1995), and they may eventually stop growing altogether (Dong et al, 1995). Under the light microscope the induced bacteria may look like 'snakes' and they may accumulate inclusion bodies (Marston, 1986).…”
Section: Introductionmentioning
confidence: 99%